The Utilization of Sketch Engine in Concordance Studies: A Corpus Linguistics Perspective - Faiza Nur Khalida; Mochamad Mui'zzudin; Ahmad Suhaili (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Corpus linguistics has developed rapidly in recent years; however, its application in Arabic language studies in Indonesia remains limited, particularly in examining the semantic distinctions of key educational terms. This study aims to investigate the distribution, collocational patterns, and semantic functions of three central terms تعليم (taʿlīm), تدريس (tadrīs), and تربية (tarbiyah) in a modern Arabic corpus, as well as their implications for conceptual meaning and language pedagogy. The novelty of this study lies in integrating corpus-based analysis of authentic linguistic data with semantic interpretation within a pedagogical framework. This research employs a qualitative descriptive approach with a corpus-based discourse analysis design, using data derived from the arTenTen24 corpus through Sketch Engine. The analysis applies frequency, concordance, and collocation techniques to identify lexical distributions and relationships. The findings reveal that تعليم is the most dominant term, primarily associated with educational systems and policy contexts; تدريس relates to instructional practices in classroom settings; while تربية encompasses broader dimensions, including values, character formation, and institutional contexts. These distinctions indicate systematic differences in semantic functions that reflect the conceptual structure of modern Arabic educational discourse. Theoretically, this study contributes to corpus-based lexical-semantic research in Arabic, while pedagogically, it supports data-driven learning to improve learners’ accuracy in using educational terminology.